Application of the Teaching at the Right Level (TaRL) Method for Back Roll Floor Gymnastics Curriculum for Class XII 8 at SMAN 2 Semarang - Ribowo, Tisna Ery; Maliki, Osa (Program Studies of Physical Education, Faculty of Teacher Training and Education, Musamus University, 2024)
Objective. This study is driven by the inadequate learning outcomes, which pose a challenge in the advancement of Physical Education, particularly at SMAN 2 Semarang. Materials and Methods. This study seeks to assess the impact of the Teaching at the Right Level (TaRL) approach on the learning outcomes of class XII 8 students regarding the back roll floor gymnastics material at SMAN 2 Semarang. This study is a Collaborative Classroom Action Research (PTKK). The study conducted is a quasi-experimental design featuring a pretest-posttest approach. A total of 36 students were randomly selected as the subjects of the study. The subjects involved in this study are participants from class XII, totaling 36 students, which includes 25 females and 11 males. The process of gathering data involved conducting interviews, making observations, reviewing documentation, and administering written tests. The employed analysis technique was quantitative descriptive. Results. The findings of the study suggest that implementing the TaRL approach has the potential to enhance student learning outcomes in the back roll floor gymnastics material for class XII 8 at SMAN 2 Semarang. Evidence from the pre-cycle indicates that student learning outcomes were at 33.33%, while cycle 1 showed an improvement to 72.22%, and cycle 2 further increased to 86.11%. Conclusion. This shows that the TaRL approach is effective in improving students' understanding of floor gymnastics.